Disain dan Pembuatan Alat Atomisasi Aluminium - Edi Iskandar; Hafrizon Hafrizon; Wiwiek Nuralimah; Hairul Arsyad; Lukmanul Hakim Arma (Jurnal Teknik Mesin Sinergi, 2020)
Metal powder is the main raw material in the manufacture of powder metallurgy-based products. Powder-making is the initial step before the powder is packed and pressed in a mold to form the desired product. This research designs and fabricates an atomizer to produce powder from liquid aluminum using a pressurized water jet system. The research stage starts from the drawing of the tool design by considering the volume of liquid aluminum, the diameter of the outlet of liquid metal, the air pressure, and the angle of attack of the water beam. The second stage is the manufacture of the atomization chamber by referring to the design drawing by making parts of the tool/frame, liquid metal feeder parts, making the walls of metal plates, making the nozzle holder, and collecting the powder parts and the water exhaust channel. The third stage is assembly, which is to unite the main parts of the aluminum atomizer. The final stage is the testing of the atomization tool using 250 Psi pressurized water with variations of attack angle was 30˚, 35˚, 40˚, 45˚, and 50˚ with a metal descending channel diameter of 5 mm. The results showed that the 45o spray angle gave the highest percentage of powder amount and the lowest 40o angle resulted in the size of aluminum metal powder in the range 0.105 mm-0.5 mm. The size of the powder was obtained at an angle of attack of 35o, which is an average of 39.5 um, and the largest size of powder was obtained at a spray angle of 40o of 89.5 um. The resulting powder form is irregular in shape, flakes (flakes), spheroid (spherical), and spongy (hollow).